PENGARUH PENGGUNAAN APLIKASI FINTECH, LITERASI KEUANGAN, DAN GAYA HIDUP DIGITAL TERHADAP PENGELOLAAN KEUANGAN PRIBADI DI ERA TEKNOLOGI - Rireh Aprilia; Nur Fatikah; Safira Puspitasari; Sunita Dasman (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
This study examines the influence of fintech applications, financial literacy, and digital lifestyle on personal financial management in the digital era, particularly among millennials and Gen Z. Using a survey of 68 respondents and multiple linear regression analysis, it was found that the use of fintech applications does not significantly impact personal financial management on its own. However, financial literacy and digital lifestyle have a significant influence. Together, these three variables account for 58.3% of the variation in personal financial management, while the remaining 41.7% is influenced by other factors. This study highlights the importance of financial literacy and understanding of digital lifestyles in personal finance.